Dietary methionine supplementation improves the European seabass (Dicentrarchus labrax) immune status following long-term feeding on fishmeal-free diets. Issue 9 (14th November 2020) - Machado, Marina; Engrola, Sofia; Colen, Rita; Conceição, Luis E. C.; Dias, Jorge; Costas, Benjamín
Abstract: Methionine is a limiting amino acid (AA) in fish diets, particularly in those containing high levels of plant protein (PP), and is key in the immune system. Accordingly, outcome on the fish immune mechanisms of methionine-deficient and methionine-supplemented diets within the context of 0 % fishmeal formulation, after a short and prolonged feeding period, was studied in European seabass ( Dicentrarchus labrax ). For this, seabass juveniles were fed a (i) fishmeal-free diet, meeting AA requirements, but deficient in methionine (MET0·65); (ii) as control, the MET0·65 supplemented with l -methionine at 0·22 % of feed weight (CTRL); (iii) two diets, identical to MET0·65 but supplemented at 0·63 and 0·88 % of feed weight of l -methionine (MET1·25 and MET1·5, respectively); and (iv) a fishmeal-based diet (FM), as positive control. After 2 and 12 weeks of feeding, blood and plasma were sampled for leucocyte counting and humoral parameter assays and head-kidney collected for gene expression. After 2 weeks of feeding, a fishmeal-free diet supplemented with methionine led to changes in the expression of methionine- and leucocyte-related genes. A methionine immune-enhancer role was more evident after 12 weeks with an increased neutrophil percentage and a decreased expression of apoptotic genes, possibly indicating an enhancement of fish immunity by methionine dietary supplementation. Furthermore, even though CTRL and FM present similar methionine content, CTRL presented a reduced expression of several immune-related genes indicating that in a practical PP-based diet scenario, the requirement level of methionine for an optimal immune status could be higher.